2021
DOI: 10.3102/00028312211058460
|View full text |Cite
|
Sign up to set email alerts
|

Did States’ Adoption of More Rigorous Standards Lead to Improved Student Achievement? Evidence From a Comparative Interrupted Time Series Study of Standards-Based Reform

Abstract: This study was designed to assess the effects of states’ adoption of more rigorous standards as part of the current wave of standards-based reform on student achievement using comparative interrupted time series analyses based on state-level NAEP data from 1990 to 2017. Results show that the effects of adopting more rigorous standards on students’ mathematics achievement were generally small and not significant. The effects on students’ reading achievement were also generally small, but negative and statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…C-SAIL also found that high-quality professional learning was associated with more aligned instruction (Edgerton & Desimone, 2018), but many teachers reported not having sufficient learning opportunities to allow them to feel fully prepared to implement the standards (Edgerton & Desimone, 2019). This finding may explain why there was little change in student achievement nationally (Song et al, 2022).…”
Section: Professional Learning That Promotes Instructional Changementioning
confidence: 99%
See 2 more Smart Citations
“…C-SAIL also found that high-quality professional learning was associated with more aligned instruction (Edgerton & Desimone, 2018), but many teachers reported not having sufficient learning opportunities to allow them to feel fully prepared to implement the standards (Edgerton & Desimone, 2019). This finding may explain why there was little change in student achievement nationally (Song et al, 2022).…”
Section: Professional Learning That Promotes Instructional Changementioning
confidence: 99%
“…Research before CCSS showed no significant relationship between alignment to content standards and test scores (Polikoff & Porter, 2014). Several studies of the impact of CCSS found generally null and sometimes negative results on achievement (Loveless, 2016; Song et al, 2022); one found positive impacts only for economically advantaged students (Bleiberg, 2021). C-SAIL found pockets of promising implementation practices, as well as evidence that high-quality support could foster better instructional alignment.…”
Section: Professional Learning That Promotes Instructional Changementioning
confidence: 99%
See 1 more Smart Citation
“…An additional charge was for C-SAIL to explore CCRS effects on teacher instruction and student performance. With respect to this last objective, Song et al (2022) focused their evaluation on states that adopted CCRS in 2010, the year in which most of them adopted the more challenging standards. Song et al divided the states into "treatment" and "comparison" states.…”
Section: Standards-based Educationmentioning
confidence: 99%
“…This past decade marked the latest wave of standards-based reforms as states adopted more rigorous standards—so-called college- and career-ready standards—intended to better prepare students for the demands of college and career after high school. A recent study conducted by Song and colleagues (Song et al, 2021), however, found that the adoption of more rigorous standards that has been the foundation of the latest standards-based reform had not yet moved the needle on student achievement based on analyses of National Assessment of Educational Progress (NAEP) data from 1990 to 2017—a conclusion consistent with the conclusion from earlier analyses conducted by Loveless (2014, 2015, 2016) about the impact of the Common Core State Standards, the dominant form of college- and career-ready standards.…”
mentioning
confidence: 99%